Glutaminase Enzyme Biosensor for Determination of Glutamine in Cerebrospinal Fluid, Human Serum and L-Glutamine Capsule - Bagriyanik, Didem Begum; Karakus, Emine (CHEM SOC PAKISTAN, 2014)
Ammonium-selective glutamine biosensor was prepared by immobilizing glutaminase on poly(vinylchloride) (PVC) ammonium membrane electrode containing palmitic acid prepared by using nonactine. The response of glutamine biosensor was linear over the concentration range of 1.0x10(-1)-1.0x10(-4)M and slope was Nernstian. We determined optimum working conditions of the biosensor such as buffer concentration, buffer pH, lifetime, response time, linear working range and other response characteristics. The optimum buffer concentration and pH of proposed glutamine biosensor were determined as 20mM and pH 7.5, respectively. The interference effects of some ions and amino acids that may be present inbody fluids were also investigated. The Km and Vmax values of glutaminase were determined. Additionally, glutamine assay in several biological samples such as healthy human serum, cerebrospinal fluid (CSF) and commercial glutamine capsule were also successfully carried out by using the standard addition method. The results were good agreement with previously reported values.
Keywords: Glutaminase; Biosensor; Glutamine biosensor; Enzyme electrode; Potentiometric; Glutamine determination; PERFORMANCE LIQUID-CHROMATOGRAPHY; AMINO-ACIDS; PLASMA; ELECTRODE; MUSCLE; Chemistry